simplify the expression.

cos^2x+sin^2x/cot^2x-csc^2x

1 answer

Parentheses are assumed missing. Implied parentheses are ALWAYS required in numerator and denominator of fractions.

(cos^2x+sin^2x)/(cot^2x-csc^2x)

This problem can be solved by converting all functions in terms of sine and cosine according to the standard definitions.

(cos^2x+sin^2x)/(cot^2x-csc^2x)
=(cos^2(x)+sin^2(x))/(cos^2(x)/sin^2(x)-1/(sin^2(x))

Use sin²(u)+cos²(u)=1 to reduce the numerator to 1.
Since the denominator has a common factor of sin²(x), we can simplify that too!

=(1)/[(cos²(x)-1)/sin²(x)]
=sin²(x)/(cos²(x)-1)
=sin²(x)/(-sin²(x)
=-1